KESEJAHTERAAN SPIRITUAL PASIEN PASCA SINDROM KORONER AKUT - Tuti Anggraini Utama; Feni Eka Dianti; Maiyulis Maiyulis (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2021)
Post-acute coronary syndrome is the rehabilitation phase that can result in physical and psychological changes that affect the quality of life of the patient which then causes psychosocial problems in the form of anxiety and depression. This anxiety and depression has a correlation with spiritual well-being. The aim of this study was to identify the level of spiritual well-being in patients after acute coronary syndrome in RS cardiac polyclinic. Dr. M.yunus Bengkulu. This research is a quantitative descriptive study using the SIWB instrument. The population of this study were all patients with SKA in 2017, totaling 250 respondents in the last 6 months. This study used accidental sampling technique, amounting to 43 respondents. The results showed that most of the patients were with low spiritual well-being (23%). In conclusion, the patient's spiritual well-being is low, so there is a need for increased fulfillment of the spiritual needs of the family.